Social inequalities – theoretical considerations from an interdisciplinary perspective - Iwona Kiniorska (Journal of Geography, Politics and Society, 2021)
Contemporary considerations on social inequalities are more and more often of an interdisciplinary character. Particular interest in the above-mentioned issues becomes noticeable in sociological and economic sciences and is also gradually increasing in geographical disciplines. The aim of this study is to present the problem of social inequalities from an interdisciplinary perspective. The analysis highlights the contribution of research conducted by representatives of sociology, economics, and geography. The methods of classification and identification of factors shaping social inequalities were also discussed.